2006
DOI: 10.1007/s00394-006-0610-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fructooligosaccharides, in spite of being fermented in the upper part of the large intestine, have anti-inflammatory activity in the TNBS model of colitis

Abstract: Previous studies have demonstrated the anti-inflammatory effect of fructooligosaccharides (FOS) on intestinal inflammation. The aim of the present study was to elucidate whether the colonic fermentation of these carbohydrates is a pre-requisite for this anti-inflammatory activity.With this aim short chain-FOS (SC-FOS) were used for an in vitro fermentation to elucidate the time of fermentation of these compounds. For the in vivo experiments female Wistar rats were fed several diets with different sources of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Several of the OTUs underrepresented in the IBD-subset are most closely related to cultured isolates of butyrate-producing bacteria (Table 1 and SI Table 5). Butyrate and other short-chain fatty acids, which are produced primarily by bacterial metabolism, are important sources of energy for colonic epithelial cells and may enhance epithelial barrier integrity and modulate the GI immune response (53)(54)(55)(56)(57)(58). Loss of similar organisms has been correlated with antibiotic-associated diarrhea in a patient (59).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the OTUs underrepresented in the IBD-subset are most closely related to cultured isolates of butyrate-producing bacteria (Table 1 and SI Table 5). Butyrate and other short-chain fatty acids, which are produced primarily by bacterial metabolism, are important sources of energy for colonic epithelial cells and may enhance epithelial barrier integrity and modulate the GI immune response (53)(54)(55)(56)(57)(58). Loss of similar organisms has been correlated with antibiotic-associated diarrhea in a patient (59).…”
Section: Discussionmentioning
confidence: 99%
“…Current dietary interventions to reduce intestine inflammation and thus, lessen the pain associated with such conditions include treatment with both macro- and micronutrients. For example, in rodent models of colitis and/or in vitro studies investigating anti-inflammatory therapeutics milk oligosaccharides, PUFAs, and polyphenolic compounds such as flavonoids are shown to significantly reduce intestinal inflammation (Lara-Villoslada, et al 2006; Vezza, et al 2016). Given this, it is a logic extension to use dietary approaches for protecting against obesity-associated intestinal inflammation.…”
Section: Nutritional Approaches For Suppression Of Obesity-associamentioning
confidence: 99%
“…We therefore assumed that these anti-inflammatory effects of SIF might be exerted through a shield-like effect against endotoxin and bacterial translocation at the early stage of colitis, leading to the reduced colonic damage 10 d after the induction of colitis. 7) A number of studies examining the effects of prebiotics, including dietary fiber and probiotics, on TNBSinduced rat colitis have already been reported, but most of them evaluated the preventive effects in the acute phase of colitis within 1-2 weeks after TNBS administration; 5,6,[9][10][11][12] the outcome was mostly successful when the treatment began before the induction of colitis. Indeed, Peran et al 6) have reported for rats that a pretreatment of Lactobacillus rutei and L. fermentum, starting 2 weeks before TNBS administration, significantly reduced colonic damage both histologically and biochemically.…”
mentioning
confidence: 99%